Serum levels of interleukin-6 in patients with primary head and neck squamous cell carcinoma - Riedel, Frank; Zaiss, Inka; Herzog, Denise Julia; Götte, Karl; Naim, Ramin; Hörmann, Karl (Anticancer research, 2005)
Interleukin (IL)-6 plays a central role as a differentiation and growth factor of tumor cells. IL-6 has been identified in a wide variety of malignancies, including head and neck squamous cell carcinomas (HNSCC). The aim of this study was to investigate the association between the serum levels of IL-6 in HNSCC patients and the biological characteristics of the tumor as well as the clinicopathological status of the patients. The circulating level of IL-6 in sera from patients with various HNSCC (n=90) as well as from healthy normal controls (n=39) was investigated. Serum IL-6 concentrations were determined as serum immunoreactivity using a quantitative sandwich enzyme immunoassay technique. For statistical analysis, the Kruskal-Wallis test was performed. The majority of the patients with HNSCC were found to have high serum IL-6 concentrations. The IL-6 levels in the sera of patients with cancer ranged from below the detection limit to 312.8 pg/ml (mean, 19.5 pg/ml). In contrast, the IL-6 serum levels in 39 healthy individuals ranged from below the detection limit to 52.2 pg/ml (mean, 6.0 pg/ml), with the concentration being significantly higher in HNSCC patients (p<0.001). Furthermore, the correlation of the IL-6 serum concentration with tumor stage was significant (p=0.04). Accordingly, there was a significant difference of IL-6 serum concentration of tumors with positive and negative lymph nodes (p=0.045), with concentration being significantly higher in lymph node-positive tumors. Our data on elevated IL-6 serum levels in the majority of HNSCC cancer patients and its correlation with tumor stage and lymph node status suggest that serum IL-6 reflects the proliferative activity of the tumor in patients with head and neck cancer. IL-6 serum determinations might serve as a biological marker and help to identify advanced head and neck tumors.
Gesehen am 01.04.2022